2011
DOI: 10.1007/s00280-011-1675-z
|View full text |Cite
|
Sign up to set email alerts
|

Modification of uptake and subcellular distribution of doxorubicin by N-acylhydrazone residues as visualised by intrinsic fluorescence

Abstract: Purpose: Doxorubicin (1) is commonly used in the treatment of a wide range of cancers. Some N-acylhydrazones of 1 were previously found to have an improved tumour and organ selectivity. In order to clarify the molecular basis for this effect, the cellular uptake into various cancer cells and the localisation in PtK 2 potoroo kidney cells of 1 and its N-acylhydrazones derived from heptadecanoic acid (2) and 11-(menthoxycarbonyl)undecanoic acid (3) were studied drawing on their intrinsic fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In keeping with our observation on the mitochondrial localization of NitDOX, it has been reported that synthetic acyl-conjugated DOXs, more hydrophobic than the parental drug, are more uptaken by drug-resistant cells and display a cytosolic rather than a nuclear localization. 35 Also, the level of ABC transporters in subcellular compartments, which is highly variable and cell type-dependent, 36−38 strongly affects the intracellular distribution of anthracyclines. In our model, the rate of nitration and extrusion activity of Pgp/ABCB1, MRP1/ABCC1, and BCRP/ABCG2 did not appear to underlie the nuclear-cytosolic partition of DOX and NitDOX.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In keeping with our observation on the mitochondrial localization of NitDOX, it has been reported that synthetic acyl-conjugated DOXs, more hydrophobic than the parental drug, are more uptaken by drug-resistant cells and display a cytosolic rather than a nuclear localization. 35 Also, the level of ABC transporters in subcellular compartments, which is highly variable and cell type-dependent, 36−38 strongly affects the intracellular distribution of anthracyclines. In our model, the rate of nitration and extrusion activity of Pgp/ABCB1, MRP1/ABCC1, and BCRP/ABCG2 did not appear to underlie the nuclear-cytosolic partition of DOX and NitDOX.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Commonly, the cellular uptake of drugs is quantified by indirect methods such as analyzing the remaining amount of drug in the supernatant of treated cultures [7]. As we have observed a Doxorubicin-induced dose dependent cellular fluorescence increase by flow cytometry, we demonstrate that a direct and precise quantification of cell-bound Doxorubicin is possible.…”
Section: Real-time High-resolution Analysis Of Cell Permeability and mentioning
confidence: 92%
“…The drug has an inherent fluorescence frequently used in a variety of different assays [2,7]. Here we use Doxorubicin as the principle model substance.…”
Section: Real-time High-resolution Analysis Of Cell Permeability and mentioning
confidence: 99%
See 2 more Smart Citations